Reduction by the Positive Allosteric Modulator of the GABAB Receptor, GS39783, of Alcohol Self-Administration in Sardinian Alcohol-Preferring Rats Exposed to the “Sipper” Procedure - Maccioni, Paola; Flore, Paolo; Carai, Mauro A.; Mugnaini, Claudia; Pasquini, Serena; Corelli, Federico; Gessa, Gian Luigi; Colombo, Giancarlo (Frontiers in Psychiatry, 2010)
The present study was designed to evaluate (a) alcohol self-administration behavior of selectively bred, Sardinian alcohol-preferring (sP) rats exposed to the so-called “sipper” procedure (characterized by the temporal separation between alcohol-seeking and -taking phases), and (b) the effect of the positive allosteric modulator of the GABAB receptor, GS39783, on alcohol self-administration in sP rats exposed to this procedure. To this end, sP rats were initially trained to lever-respond under a reinforcement requirement (RR) 55 (RR55) for alcohol. Achievement of RR55 resulted in the 20-min presentation of the alcohol (15%, v/v)-containing sipper bottle. Once stable levels of lever-responding and alcohol consumption were reached, rats were treated with 0, 25, 50, and 100 mg/kg GS39783 (i.g.) 60 min before the self-administration session. Rats displayed robust alcohol-seeking (as suggested by relatively short latencies to the first lever-response and high frequencies of lever-responding) and -taking (as suggested by alcohol intakes averaging approximately 1.5 g/kg) behaviors. Pretreatment with GS39783 inhibited both alcohol-seeking (the number of rats achieving RR55 and the mean RR value were virtually halved) and -taking (the amount of self-administered alcohol was reduced by approximately 60%). The results of the present study suggest the power of the “sipper” procedure in triggering high levels of alcohol-seeking and -taking behavior in sP rats. Further, these results extend to this additional procedure of alcohol self-administration the capacity of GS39783 to reduce the motivational properties of alcohol and alcohol consumption in sP rats.